2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--28462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Course Structure on Learning and Self-Efficacy in a Unit Operations Laboratory

Abstract: IntroductionIn the chemical engineering curriculum, the unit operations laboratory course traditionally serves several key roles in the development of students as professional engineers. The primary goal of the course is to apply chemical engineering theory learned in core courses to the operation of equipment. As part of this process, however, numerous additional skills are often also learned and/or emphasized: experimental design, instrumentation, technical communication, teamwork, and critical thinking, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…A survey of United States chemical engineering programs reported that most of the unit operation laboratories are designed with the following learning objectives: (1) demonstrate ethical responsibilities in the laboratory; (2) acquire knowledge of the design of experiments and instrumentation; (3) demonstrate creativity, effective communication, and critical thinking; and (4) practice data analysis and teamwork [16]. The structure and implementation of these laboratory courses have an impact on student motivation and engagement.…”
Section: Survey Of Existing Laboratory Course Gamesmentioning
confidence: 99%
“…A survey of United States chemical engineering programs reported that most of the unit operation laboratories are designed with the following learning objectives: (1) demonstrate ethical responsibilities in the laboratory; (2) acquire knowledge of the design of experiments and instrumentation; (3) demonstrate creativity, effective communication, and critical thinking; and (4) practice data analysis and teamwork [16]. The structure and implementation of these laboratory courses have an impact on student motivation and engagement.…”
Section: Survey Of Existing Laboratory Course Gamesmentioning
confidence: 99%
“…This laboratory course is typically the first time many chemical engineering students have the opportunity to work with pilot-scale equipment, facilitating a unique laboratory practice and experiential learning experience during their undergraduate career [1]. Additional professional skills are developed by students working in the laboratory, including teamwork, experimental designs, technical written and oral communication, and critical thinking [2]- [4]. The combination of practical and professional skills within the Unit Operations laboratory could successfully allow students to complete experiential learning within their undergraduate curriculum.…”
Section: Introductionmentioning
confidence: 99%